2013
DOI: 10.1645/ge-3183.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Ixodid Ticks Parasitizing Eastern Mouse and Dwarf Lemurs in Madagascar, with Descriptions of the Larva, Nymph, and Male ofIxodes lemuris(Acari: Ixodidae)

Abstract: The ixodid ticks parasitizing small-bodied nocturnal mouse and dwarf lemurs (Primates, Cheirogaleidae) in Madagascar are poorly documented. At Tsinjoarivo, a high-altitude eastern rain forest, mouse and dwarf lemurs were parasitized by ixodid ticks. At Ranomafana, a montane southeastern rain forest, dwarf lemurs hosted a species of Ixodes, whereas mouse lemurs were parasitized by Haemaphysalis lemuris. Ixodes specimens represent all active stages, and females are morphologically consistent with previous descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The original descriptions of H. elongata and H. simplex [ 64 ], H. obtusa [ 65 ] and H. hoodi madagascariensis [ 66 ] were complemented by the description of nine new species ( H. anoplos , H. eupleres , H. fossae , H. lemuris , H. nesomys , H. simplicima , H. subelongata , H. theilerae and H. tiptoni ) [ 39 – 43 ]. More recent studies [ 20 – 22 , 67 ] identified collected tick specimens based on these descriptions and complementary cox 1 gene sequences were generated for H. lemuris by Blanco et al [ 68 ]. Assuming a correct classification in this previous study, our collected tick specimens showed distinct genetic differences (only 85% nucleotide identity with published H. lemuris sequences obtained from a M. rufus host), even though morphological characteristics visualized by light microscopy resembled the description of H. lemuris .…”
Section: Discussionmentioning
confidence: 99%
“…The original descriptions of H. elongata and H. simplex [ 64 ], H. obtusa [ 65 ] and H. hoodi madagascariensis [ 66 ] were complemented by the description of nine new species ( H. anoplos , H. eupleres , H. fossae , H. lemuris , H. nesomys , H. simplicima , H. subelongata , H. theilerae and H. tiptoni ) [ 39 – 43 ]. More recent studies [ 20 – 22 , 67 ] identified collected tick specimens based on these descriptions and complementary cox 1 gene sequences were generated for H. lemuris by Blanco et al [ 68 ]. Assuming a correct classification in this previous study, our collected tick specimens showed distinct genetic differences (only 85% nucleotide identity with published H. lemuris sequences obtained from a M. rufus host), even though morphological characteristics visualized by light microscopy resembled the description of H. lemuris .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, only a few African Ixodes species had available sequences in GenBank, especially from the subgenus Afrixodes (i.e. Ixodes pilosus , I. bakeri , I. fynbosensis : [ 7 ]; I. aulacodi : [ 41 ], I. lemuris : [ 31 ]). The complete mitogenome is also available for a few species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences from other studies (retrieved from GenBank) included in the phylogenetic analyses had nearly or exactly 100% coverage with sequences from this study. Therefore, although very few sequences of Afrixodes were previously deposited in GenBank, some of them had to be excluded because of their shortness ( Ixodes lemuris : JX470176 [ 31 ]; I. corwini : AF113926 [ 32 ]). In addition, unpublished sequences of two Ixodes samples used in a previous study ([ 33 ]: I. ricinus , I. trianguliceps ) were included to improve the phylogeny of Ixodes subgenera that are not present in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, mouse lemurs are parasitized by multiple species of ticks. These small primates primarily present immature tick stages ( Durden et al., 2010 , Rodriguez et al., 2012 , Blanco et al., 2013 ) and likely serve as maintenance hosts to various three-host tick species, including Haemaphysalis lemuris , Ixodes lemuris ( Blanco et al., 2013 ), and other Haemaphysalis spp. ( Durden et al., 2010 , Rodriguez et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%